2016
DOI: 10.1074/jbc.m116.731331
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Activation Is Regulated by Epidermal Growth Factor-like Domain 7 (Egfl7) during Inflammation

Abstract: Edited by Dennis VoelkerActivation of the blood vessel endothelium is a critical step during inflammation. Endothelial cells stimulated by pro-inflammatory cytokines play an essential part in the adhesion and extravasation of circulating leukocytes into inflamed tissues. The endothelial egfl7 gene (VE-statin) represses endothelial cell activation in tumors, and prior observations suggested that it could also participate in the regulation of endothelial cell activation during inflammation. We show here that Egf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…This NF-kB-dependent inflammatory activation of ECs is regulated by EGFL7 via preservation of IkB-α and subsequent sequestration of NF-kB, which has been shown to downregulate ICAM-1 in human coronary ECs 24 . Our human in vitro and EAE in vivo data demonstrate that MCAM expression, rather than ICAM-1 or VCAM-1 as previously reported in peripheral endothelium 12 , 25 , is subjected to regulation by EGFL7 in BBB-ECs. This difference could depend on the type of cytokines present, which can impact both CAM and EGFL7 expression, on the type of endothelium and on the influence of astrocytic factors in vivo.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This NF-kB-dependent inflammatory activation of ECs is regulated by EGFL7 via preservation of IkB-α and subsequent sequestration of NF-kB, which has been shown to downregulate ICAM-1 in human coronary ECs 24 . Our human in vitro and EAE in vivo data demonstrate that MCAM expression, rather than ICAM-1 or VCAM-1 as previously reported in peripheral endothelium 12 , 25 , is subjected to regulation by EGFL7 in BBB-ECs. This difference could depend on the type of cytokines present, which can impact both CAM and EGFL7 expression, on the type of endothelium and on the influence of astrocytic factors in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Although effects of EGFL7 on proliferation and activation of immune cells have not been reported so far, EGFL7 expression was associated with a reduced immune infiltration in breast cancer 11 . In line with this, EGFL7 was recently implicated in the regulation of peripheral EC activation through repression of the NF-κB pathway 12 .…”
Section: Introductionmentioning
confidence: 73%
“…Epidermal growth factor‐like domain 7 (EGFL7) is an angiogenic factor exclusively expressed in ECs and controls key steps in vascular tube formation 60 . EGFL7 also represses endothelium activation during inflammatory conditions, and activated endothelium plays an essential part in the adhesion and transendothelial migration of circulating leukocytes into inflamed vascular tissues 61 . We found that EGFL7 mRNA level is significantly reduced in freshly isolated JAK2V617F‐mutant cardiac ECs compared to wild‐type ECs (Figure 5D).…”
Section: Resultsmentioning
confidence: 90%
“…As the CVD phenotype does not present in Tie2FF1 mice until after ~20 weeks of age ( Figure 1A), we isolated primary murine cardiac ECs into inflamed vascular tissues. 61 We found that EGFL7 mRNA level is significantly reduced in freshly isolated JAK2V617F-mutant cardiac ECs compared to wild-type ECs (Figure 5D).…”
Section: Jak2v617f-mutant Ecs Display a Vasculopathy Phenotypementioning
confidence: 78%
See 1 more Smart Citation